The Conserved Polarity Factor PodJ1 Impacts Multiple Cell Envelope-Associated Functions in Sinorhizobium meliloti - Fields, Alexander T. (2012)
Although diminutive in size, bacteria possess highly diverse and spatially confined cellular structures. Two related alpha-proteobacteria, Sinorhizobium meliloti and Caulobacter crescentus, serve as models for investigating the genetic basis of morphologic variations. S. meliloti, a symbiont of leguminous plants, synthesizes multiple flagella and no prosthecae, whereas C. crescentus, a freshwater bacterium, has a single polar flagellum and stalk. The podJ gene, originally identified in C. crescentus for its role in polar organelle development, is split into two adjacent open reading frames, podJ1 and podJ2, in S. meliloti. Deletion of podJ1 interferes with flagellar motility, exopolysaccharide production, cell envelope integrity, cell division, and normal morphology, but not symbiosis. As in C. crescentus, the S. meliloti PodJ1 protein appears to act as a polarity beacon and localizes to the newer cell pole. Microarray analysis indicates that podJ1 affects the expression of at least 129 genes, the majority of which correspond to observed mutant phenotypes. Together, phenotypic characterization, microarray analysis, and suppressor identification suggest that PodJ1 controls a core set of conserved elements, including flagellar and pili genes, the signaling proteins PleC and DivK, and the transcriptional activator TacA, while alternate downstream targets have evolved to suit the distinct lifestyles of individual species.